PcFKH1, a novel regulatory factor from the forkhead family, controls the biosynthesis of penicillin in Penicillium chrysogenum - Domínguez-Santos, Rebeca; García-Estrada, Carlos; Kosalková, Katarina; Prieto, Carlos; Santamarta, Irene; Martín, Juan-Francisco (Biochimie, 2015)
Penicillin biosynthesis in Penicillium chrysogenum (re-identified as Penicillium rubens) is a good example of a biological process subjected to complex global regulatory networks and serves as a model to study fungal secondary metabolism. The winged-helix family of transcription factors recently described, which includes the forkhead type of proteins, is a key type of regulatory proteins involved in this process. In yeasts and humans, forkhead transcription factors are involved in different processes (cell cycle regulation, cell death control, pre-mRNA processing and morphogenesis); one member of this family of proteins has been identified in the P. chrysogenum genome (Pc18g00430). In this work, we have characterized this novel transcription factor (named PcFKH1) by generating knock-down mutants and overexpression strains. Results clearly indicate that PcFKH1 positively controls antibiotic biosynthesis through the specific interaction with the promoter region of the penDE gene, thus regulating penDE mRNA levels. PcFKH1 also binds to the pcbC promoter, but with low affinity. In addition, it also controls other ancillary genes of the penicillin biosynthetic process, such as phlA (encoding phenylacetyl CoA ligase) and ppt (encoding phosphopantetheinyl transferase). PcFKH1 also plays a role in conidiation and spore pigmentation, but it does not seem to be involved in hyphal morphology or cell division in the improved laboratory reference strain Wisconsin 54-1255. A genome-wide analysis of processes putatively coregulated by PcFKH1 and PcRFX1 (another winged-helix transcription factor) in P. chrysogenum provided evidence of the global effect of these transcription factors in P. chrysogenum metabolism. •A novel transcription factor, PcFKH1, has been characterized in P. chrysogenum.•PcFKH1 controls the expression of the penDE gene and penicillin biosynthesis.•Conidiation and pigmentation seem to be controlled by PcFKH1.•A global analysis of processes putatively regulated by PcFKH1 has been carried out.